Local synthesis and function of neuro-estrogen and neuro-androgen: impact on the hippocampus-related cognition and neuronal plasticity - Kawato, Suguru; Hojo, Yasushi; Soma, Mika; Horie, Shigeo; Saito, Minoru; Ogiue-Ikeda, Mari (Frontiers in Cellular Neuroscience, 2026)
Brain sex neurosteroids have been attracted much attention, because the brain itself can synthesizes a sufficient amount of sex neurosteroids independent of circulating sex steroids. Local synthesis and action of neuro-estrogen [such as neuro-estradiol (nE2)] and neuro-androgen [such as neuro-testosterone (nT) and neuro-dihydrotestosterone (nDHT)] have become recognized as key factors in modulation of synaptic plasticity, cognitive performance, and protection of aging dependent decline of neurological functions. Unlike circulating sex steroids, these locally synthesized sex neurosteroids can directly and rapidly modulate neuronal synapses and induce potent effects on learning and memory. The properties of local neurocrine systems are significantly different from those of classical neuroendocrine systems dependent on the hypothalamic–pituitary-gonadal axis. For example, in the hippocampus, not only neuro-androgen (nT and nDHT) but also nE2 have higher concentrations than testis-derived circulating androgen (T and DHT) and ovary-derived circulating E2 (cir-E2). In addition, male nE2 concentration is higher than female nE2 at both adult stage and newborn stage during which brain masculinization occurs. Over the past decades, numerous experimental results and interpretations of sex neurosteroids have been shown. However, in several cases, these results and interpretations are mutually conflicting, and a unified understanding has not yet been achieved. Therefore, we here deeply discuss several critical and important issues toward solving complex problems to understand. We focus the following issues. First (A) Local synthesis of nE2, nT and nDHT, with particular attention to their concentrations, synthesis pathways and sex differences in rodents. Higher nE2 concentration in male hippocampus than in female in adult stage. Then (B) Comparison of modulation of long-term potentiation (LTP) by nE2 and nDHT. Stimulatory effects of nE2 on LTP which are mediated by membrane estrogen receptor ER and protein kinase signaling. Inhibitory effects of nDHT on LTP which are mediated by membrane androgen receptor AR. Third (C) Both nE2 and nDHT show the same rapid increases in dendritic spines. Their effects on spinogenesis are very different from their effects on LTP. Fourth (D) Rapid effects of nE2 and nT on cognitive behavior. Male signaling pathway may be more complex than female signaling pathway. Finally (E) Aging-dependent cognitive decline which is dependent on decrease of nT in male and nE2 in female. T-replacement therapy of male patients shows improvement in spatial cognitive decline. E2-replacement therapy improves female cognitive decline.